Response to the Contested Language Forum - Small, Helen (Age, Culture, Humanities: An Interdisciplinary Journal, 2023)
This 'Credo' essay responds to the Contested Terms Forum (Issue 6), exploring why the language used about ageing gives rise to arguments, and examining the particular pressures placed on academic and broader public discourse by geography, regionality, cultural context and, not least, age. Drawing on Deborah Cameron's thinking about 'verbal hygiene', as it sheds light on the social context of all language use and the inevitability of divergent views about 'norms', the essay probes particular points of pressure on discourses of ageing at present. Two recent publications, Wendy Mitchell's What I Wish People Knew about Dementia (2022) and Pope Lonergan's I'll Die After Bingo (also 2022), help to unpack the importance of flexible attitudes to language within care settings. The essay then considers the focus on language as a defining feature of Humanistic study—an element of its critical 'deformation' (in the neutral sociological sense) by contrast with the Social and Medical Sciences. Attention is also given to the forms of flexibility required by literary criticism in its dealings with texts, which will often have historic, dramatic, psychological, emotional or other rationales for employing language that would rightly be rebuked in real-world social settings. Submitted: 21 February 2023 Published: 19 June 2023